ANALYSIS OF ACOUSTIC WAVE PROPAGATION IN AN INFINITE COAXIAL DUCT WITH A PARTIAL ABSORBING INTERNAL SURFACE - Ozturk, Hulya (Univ Politehnica Bucharest, Sci Bull, 2022)
The propagation of acoustic waves along a rigid infinite coaxial duct with a partial lining on the outer wall is developed by using the mode-matching technique. This technique is based on deriving the solution in the way of an infinite sum of orthogonal functions and then matching them across the boundaries between the regions. In addition to the analytical derivations, the affects of the parameters such as waveguide radii, surface impedance and its length on the propagation phenomenon are presented. The problem is also compared numerically with the Wiener-Hopf approach which is more difficult to implement and very good agreement is obtained. This model can be used as a dissipative silencer which makes a significant contribution for reducing unwanted noise.
Keywords: Mode -matching method; coaxial duct; acoustics; absorbent lining